THEILERIOSIS IN NEWBORN CALVES IN MOSUL, IRAQ - E.G.Suleiman; K.M. Alsaad; Q.T. Al-Obaidi (Basrah Journal of Veterinary Research)
The objective of the present study were to evaluate hemogram, acute phase response, acid base balance and blood gas analysis in newborn calves infected with Theileria annulata . The study was conducted on 55 local newborn calves (male and female), 1-9 days old. The study was carried out in Mosul , Iraq. Forty five newborn calves were infected with Theileria annulata. and Ten clinically normal calves served as controls. Diseased calves showed sings of fever ,unilateral or bilateral visible swelling of superficial lymph nodes. pronounced upward bulging of temporal fossa, outward bulge of conjunctivae with exophthalmos, paleness and/or icteric mucus membranes with petechial hemorrhages on the conjunctiva, lacrimation, dyspnea and depression. There was a significant reduction in the mean values of erythrocytes count, Hb and PCV,in diseased newborn calves infected with Theileria annulata and anemia was of Macrocytic hypochromic type. The percentage of hemoparasitism (parasitemia) ranged between (3-18%) with a mean of (11.88%). Results also indicated significant increase in total leukocytes count as results of significant increase lymphocytes. Diagnosis of Theileriosis were confirmed by microscopical examination of Giemsa stained lymph node aspirate and peripheral blood smears. Results were also showed significant decrease in blood pH,Pco2,Bicarbonate, Base access and Oxygen saturation percent(So2) ,However significant increase in Anion gab was found and Titritional metabolic acidosis were indicated. Moreover results show significant decrease in haptoglobin and fibrinogen in diseased newborns calves than in controls.It have been concluded that Theileria annulata infection in newborn calves resulting in serious effects and health deterioration, leading to substantial significant economic losses